2021
DOI: 10.1177/21582440211064899
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Relationship Between China-Africa Trade, China OFDI, and Economic Growth of African Countries

Abstract: Recently, China has emerged as the largest trading partner and a significant source of investment in the African continent. Although there is consent on the increasing importance of China and Africa’s economic partnership, there are many controversies on how it affects African countries. Debates on China in Africa have, however, relied on grandiloquence rather than empirical studies. This study explores the causal link between China-Africa trade, China’s outward foreign direct (OFDI), and economic growth of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 74 publications
(130 reference statements)
0
7
1
Order By: Relevance
“…This suggests that outward FDI has a negative impact on economic growth, wherein a 1 per cent increase in outward FDI will entail a reduction in economic growth of approximately 0.443 per cent. This finding is inconsistent with the results of Amin et al (2020) and Obobisa et al (2021), who disclosed that for many developing economies, economic growth responds positively and significantly to upswings in FDI outflows. This is, therefore, a wakeup call for ASEAN-8 countries to give special attention to outward investments and implement economic policies that encourage growth in sectors to realise the benefits of outward investment on economic growth.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…This suggests that outward FDI has a negative impact on economic growth, wherein a 1 per cent increase in outward FDI will entail a reduction in economic growth of approximately 0.443 per cent. This finding is inconsistent with the results of Amin et al (2020) and Obobisa et al (2021), who disclosed that for many developing economies, economic growth responds positively and significantly to upswings in FDI outflows. This is, therefore, a wakeup call for ASEAN-8 countries to give special attention to outward investments and implement economic policies that encourage growth in sectors to realise the benefits of outward investment on economic growth.…”
Section: Resultscontrasting
confidence: 95%
“…The effects of outward FDI on economic growth have been well documented by, amongst others. Outward FDI has greatly increased the economic growth of African countries, according to Obobisa et al (2021). Furthermore, Amin et al (2020) offered compelling evidence that outward FDI has a favourable and significant impact on Romania's economic growth, with the increase in outward FDI having a higher impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, FGLS has been used in many different contexts (see for instance, Refs. [ [64] , [65] , [66] , [67] , [68] , [69] ]).…”
Section: Methodsmentioning
confidence: 99%
“…In the same vein, Donou-Adonsou & Lim (2018) investigated the effect of China's FDI on economic growth in African countries and revealed that China's FDI contributes to the increase in income per capita and welfare in Africa, especially in Francophone countries. Obobisa et al (2021) explored the nexus between China's outward foreign direct (OFDI), and the economic growth of 24 Sub-Saharan African nations from 1999 to 2018. The results of the feasible generalized least squares (FGLS) method disclosed that Chinese OFDI positively affected economic growth in low-middle and low-income African countries.…”
Section: Chinese Ofdi and Economic Growthmentioning
confidence: 99%